2023
DOI: 10.3390/healthcare11040495
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Practices and Adoption of National Family Planning Communication Campaigns on Select Ethnic Groups in Nigeria

Abstract: This study evaluated the extent to which married Idoma (Benue State) and Igala people (Kogi State) in North-Central Nigeria were exposed to the 2017 National Family Planning Communication Campaigns. The study also examined their level of knowledge, the extent to which they adopted the campaign messages, and how Alekwu/Ibegwu and other socio-cultural factors influenced their level of adoption of the campaign messages. The study adopted a quantitative (questionnaire survey) research method. The data were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…If the patriarchal culture is strong, women generally obey their husbands. Culture believed by people, such as husbands or other family members, will affect women's ways of thinking and decisions to use contraception [36]. This study shows that most women do not live in strong patriarchal situations.…”
Section: Resultsmentioning
confidence: 77%
“…If the patriarchal culture is strong, women generally obey their husbands. Culture believed by people, such as husbands or other family members, will affect women's ways of thinking and decisions to use contraception [36]. This study shows that most women do not live in strong patriarchal situations.…”
Section: Resultsmentioning
confidence: 77%
“…Household barriers to the utilization of IMNCH services exist among married women who may rely on financial support from their husbands, thereby posing barriers to the utilization of these services [ 19 ]. Some studies have also shown that men (who are culturally responsible for upholding their local beliefs) often discourage women from utilizing services such as family planning methods in favor of their cultural beliefs [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Education is a long-established determinant of the demand for reproductive healthcare, including self-awareness of the need for reproductive health services [ 17 ]. Studies have shown that the limited uptake of modern contraceptive use in Benue State is due to overriding cultural beliefs despite high levels of knowledge and higher educational levels being associated with a better uptake of family planning methods [ 20 , 22 , 23 ]. Some of the cultural beliefs (in Alekwu and Ibegwu) described include that a woman is married for the purpose of children, a deity would help them in spacing out their children and that contraception amounts to killing the unborn child [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations